Issues in foreign workers management in construction project / Muhammad Ashrof Arifuddin Zakaria and Fairiz Miza Yop Zain - Zakaria, Muhammad Ashrof Arifuddin; Yop Zain, Fairiz Miza (2020)
Hiring foreign workers have their pros and cons toward construction team. Despite it can fulfil the construction sector needs, it leave a challenges toward contractors in managing foreign workers. Project managers and team leaders face difficulties in handling foreign workers. Project managers need to prepare sets of skilled with diversity management skill and knowledge to lead foreign workforce effectively. The main issues are foreign workers who willing to works do not really have sufficient knowledge in construction. The contractor main problem in managing foreign workers is to boost the productivity and quality of works from foreign workers. Other barrier to contractor is communication barrier which is different in languages. Therefore, the aim of this research is to manage and reduced the challenges in hiring foreign workers in construction because of many foreign workers recruited in Malaysia construction industry. The objectives of the research are to identify the contractor challenges in managing foreign workers, to study the impact of hiring foreign workers to contractors and to find the solution for the problems in managing foreign workers. A questionnaire survey has been distributed among the contractors and 38 valid data answered by the respondents were analysed. The result of this study is presented in the form of quantitative analysis which is frequency and percentages analysis. It can be concluded that contractor does have issues in managing foreign workers. It is also leaves an impact towards contractor itself. As whole, this research identify the challenges in managing foreign workers, the impact of hiring foreign workers and lastly is suggesting the solution for contractor to manage and reduced the challenges in managing foreign workers.